Phytosociological analysis on the national park of the Tek Tek mountains, ?anliurfa, Turkey (Bangladesh Journal of Botany, 2014)
Vegetation of the national park of Tek Tek Mountains under the semi-arid and cool Mediterranean climate was analyzed according to 'Braun-Blanquet approach'. The plant associations are classified by considering the characteristic features of the species. In the national park, one new association (Ceraso tortusae - Pistacietum palaestinae) belonging to the shrub vegetation, and two new associations (Achilleo aleppicae - Centaureetum virgatae and Eryngietum cretico virentis) belonging to steppe vegetation were determined. No similarity among these associations has been identified in the study area with any others introduced before was found. Therefore, these syntaxa are new for science. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19742 Bangladesh J. Bot. 43(1): 27-35, 2014 (June)